Studies on genetic variability in linseed (Linum usitatissimum L.): Studies on genetic variability in linseed (Linum usitatissimum L.) - NALINI TEWARI; ACHILA SINGH (Journal of Oilseeds Research, 2018)
The field experiment was conducted during winter season of 2012-13 at C.S. Azad University of Agriculture and Technology, Kanpur with 73 genotypes including checks Shekhar and T-397 to study the genetic variability in linseed. A wide range of variability was observed for all the traits under study. The phenotypic coefficient of variation (PCV) and genotypic coefficient of variation (GCV) estimates were high for seed yield per plant and number of secondary branches per plant. High heritability was observed for all the traits except oil content and 1000-seed weight. High heritability coupled with high genetic advance as per cent of mean was recorded for seed yield per plant, number of secondary branches per plant, number of primary branches per plant and number of capsules per plant.